Development of Rapid Tooling Material Formula Based on Aluminum Filled Epoxy Resin - Yang, Guang; Ma, Shi-Xiong; Yue, Yan-Fang; Zhang, Yong-Di; He, Lin-Nan (Asian Journal of Chemistry, 2014)
This paper examined a new pouring process that utilized an aluminum filled epoxy resin rapid tooling material.The pouring parameters were optimized through variances in the amount of curing agent, diluent and filler. The study comprised of four factors and three orthogonal levels. The optimal formula was determined through range analysis, fracture morphology through scanning electron microscopy (SEM) and analysis of the material combination between the internal interfaces. Aluminum filled epoxy resin materials presented optimized mechanical performance for use as mold materials.